Early contract renegotiation: An analysis of US labor contracts form 1970 to 1995 - Robert Rich; Joseph Tracy (Federal Reserve Bank of New York, 2011)
This paper examines the ex post flexibility of U.S. labor contracts during the 1970-95 period by investigating whether unanticipated changes in inflation increase the likelihood of a contract being renegotiated prior to its expiration. We find strong empirical support for this hypothesis. Specifically, our results indicate that renegotiations are triggered principally by large and infrequent price shocks of either sign. When combined with evidence that ex ante contract durations are shorter during episodes of increased inflation uncertainty, our results suggest that these contracts are flexible both ex ante and ex post to changes in the evolution of inflation.
Keywords: E24; J41; J51; 330; labor contract; early renegotiation